Development of Business Process Based on Risk in Procurement Process of High-Rise Vertical Housing to Improve Performance Time in The Ministry of Public Works and Housing - Marendi Rahman; Muhammed Ali Berawi (Journal of International Conference Proceedings (JICP), 2021)
The implementation of the construction of vertical housing has a record that there are still many experience delays in completing work. One of the contributing factors is the imperfect procurement process. Therefore, it is necessary to develop business processes in the procurement process. This study aims to develop a business process base on risk in the process of procuring high-rise vertical housing to improve performance time. Qualitative risk analysis is carried out to determine the highest risk and use the risk response to analyze its business process development actions. The results obtained are in the form of the highest risk in the procurement process and the development of the procurement business process.